2022
DOI: 10.1149/1945-7111/ac9bdc
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Pd Intermetallics using Hg-In by the Electrochemical Liquid-Liquid-Solid Method

Abstract: Electrodeposition of Pd from alkaline baths containing Pd(CN)2 and KCN with liquid metal electrodes has been performed. Data are presented that Pd dissolved into and reacted with the liquid metal electrodes via an electrochemical liquid-liquid-solid (ec-LLS) process. HgPd crystals were obtained with liquid Hg electrodes. On solid In electrodes, In7Pd3 was exclusively formed. In contrast, InPd was the primary product with Hg1-xInx alloy electrodes. X-ray diffraction, scanning electron microscopy, and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…This was placed at about L 2 = 40 cm from the sample in a position close to one of the tank walls. The webcam was controlled through the specialized SkyStudio Pro software [ 28 ] to take pictures every 10 minutes over the course of each experiment. The laser, lamp and electric motor (see Fig 1 ) were connected to an Arduino UNO board to control the switching on and off of each of these elements (more details on the electrical connections can be found in S2 Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…This was placed at about L 2 = 40 cm from the sample in a position close to one of the tank walls. The webcam was controlled through the specialized SkyStudio Pro software [ 28 ] to take pictures every 10 minutes over the course of each experiment. The laser, lamp and electric motor (see Fig 1 ) were connected to an Arduino UNO board to control the switching on and off of each of these elements (more details on the electrical connections can be found in S2 Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, we targeted the ec-LLS synthesis of In–Pd intermetallics . Such compounds are interesting as selective hydrogenation catalysts .…”
Section: Influence Of the Local Atomic Structure And Composition Of L...mentioning
confidence: 99%
“…(e) Schematic depiction of the formation of In–M intermetallics by ec-LLS. Adapted with permission from ref . Copyright 2022 The Electrochemical Society.…”
Section: Influence Of the Local Atomic Structure And Composition Of L...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an entirely different electrodeposition strategy for intermetallic synthesis was demonstrated that involved liquid metal electrodes [23] . Based off of the electrochemical liquid‐liquid‐solid (ec‐LLS) concept, [24] this recent report blended electroreduction with melt crystal growth.…”
Section: Introductionmentioning
confidence: 99%